Pola Interaksi Pengguna TikTok pada Akun @JVKE - Russel; Doddy Salman (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study analyses the patterns of interaction between internet users (netizens) and music promotional content on the TikTok account @jvke using a descriptive qualitative approach. Data was obtained through online observation of four popular pieces of content on the @jvke account. The content was analysed to identify reception patterns such as dominant-hegemonic, negotiated, and oppositional. The results of this study indicate that the majority of netizens gave dominant-hegemonic responses, meaning that the messages were received in line with and in accordance with the messages from the promotional content uploaded by JVKE. Some netizens gave comments with negotiated responses, or gave personal interpretations and suggestions. Meanwhile, the rest gave oppositional responses. The author provides recommendations for music industry players to explore creativity in designing music marketing content strategies on TikTok. Penelitian ini menganalisis pola interaksi pengguna internet (netizen) terhadap konten promosi musik pada akun TikTok @jvke dengan menggunakan pendekatan kualitatif deskriptif. Data diperoleh melalui observasi online pada empat konten populer di akun @jvke. Konten dianalisis untuk mengidentifikasi pola resepsi seperti dominant-hegemonic, negotiated, dan oppositional. Hasil penelitian ini menunjukkan bahwa mayoritas netizen memberikan respons dominant-hegemonic artinya bahwa pesan diterima sejalan dan sesuai terhadap pesan dari konten promosi yang di unggah oleh JVKE. Beberapa netizen memberikan komentar dengan respon negotiated, atau memberikan interpretasi dan saran pribadi. Sementara sisanya memberikan tanggapan oppositional. Penulis memberikan rekomendasi untuk para pelaku industri music agar mengeksplorasi kreatifitas untuk merancang strategi konten pemasaran musik di TikTok.